2017
DOI: 10.1039/c6ra28847b
|View full text |Cite
|
Sign up to set email alerts
|

Fracture behaviors of monolithic lithium disilicate ceramic crowns with different thicknesses

Abstract: The present in vitro study assessed the fracture resistance of monolithic ceramic crowns, made from two lithium disilicate glass ceramics with different thicknesses. Sixty monolithic ceramic crowns with different thicknesses (0.5 mm, 0.8 mm, 1.0 mm, 1.2 mm, and 1.5 mm respectively, n ¼ 6 for each thickness group) were fabricated with IPS e.max Press (EMAX) and an experimental lithium disilicate ceramic (ELDC), respectively. All crowns were luted on the PMMA abutments with resin cement. Fracture load value (F(u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
1
16
0
2
Order By: Relevance
“…Regarding the results of this research, all groups in this study showed a clinically acceptable marginal fit below 100 µm [10,11] The results proved that regardless the type of the milling device used, there was a significant increase in the marginal fit with 0.5 mm thickness laminate veneers in X5I, CMI and XLI subgroups. This finding was consistent with results showed by Yu et al [22], who concluded that the increased thickness of the ceramic can contribute to reducing the crack initiation within the ceramic and so increasing the marginal fracture resistance during milling. So, the first null hypothesis was rejected.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the results of this research, all groups in this study showed a clinically acceptable marginal fit below 100 µm [10,11] The results proved that regardless the type of the milling device used, there was a significant increase in the marginal fit with 0.5 mm thickness laminate veneers in X5I, CMI and XLI subgroups. This finding was consistent with results showed by Yu et al [22], who concluded that the increased thickness of the ceramic can contribute to reducing the crack initiation within the ceramic and so increasing the marginal fracture resistance during milling. So, the first null hypothesis was rejected.…”
Section: Discussionsupporting
confidence: 93%
“…This difference in fracture pattern could be caused by the reduced thickness of ceramic at the load contact area and angulation of contact stresses inherent to the FE preparation 47 . This is supported by the results of an in vitro study that showed that the thickness of monolithic lithium disilicate ceramic crowns was responsible for such failures, and they recommended a minimum thickness of 1.0 to 1.2 mm 59 …”
Section: Discussionmentioning
confidence: 83%
“…The easy generation and propagation of radial cracks within thinner crowns cause catastrophic fractures, while the cone crack mechanism is predominantly observed in thicker crowns. 22 Harvey et al 23 suggested that the cone-crack fracture of glass-ceramic restorations requires a higher load leading to bulk fracture.…”
Section: Discussionmentioning
confidence: 99%